Catena-Poly[[bis(pyridine-κN)zinc]-μ-5-carboxybenzene-1, 3-dicarboxylato-κ2 O 1:O 3] - Yotnoi B. (2014)
The title one-dimensional coordination polymer, [Zn(C9H 4O6)(C5H5N)2] n or [Zn(HBTC)(py)2]n , (I), where BTC is benzene-1,3,5-tricarboxylate and py is pyridine, is a solvent-free polymorph of [Zn(HBTC)(py)2]·2C2H5OH [Yaghi et al. (1997). Chem. Mater. 9, 1074-1076]. Differences in the spatial arrangements and supramolecular packing of the [Zn(HBTC)(py)2]n chains in the two structures are described. The chain in (I) extends parallel to [100] and is severely puckered, with a Zn⋯Zn distance of 8.3599 (3) Å and a Zn⋯Zn⋯Zn angle of 107.516 (3)°, as a result of hydrogen-bonding interactions of the types O - H⋯O and C - H⋯O. There is no evidence for π-π interactions in (I). The differences between the solvent-free and solvent-containing structures can be accounted for by the absence of the ethanol solvent molecule and the use of the converging pair of O atoms in the bis-monodentate bridging HBTC2- ligand in (I). © Yotnoi and Rujiwatra 2013.